EXPLORING THE ROLE OF NUCLEAR-BASED TECHNOLOGIES IN ENHANCING SECURITY AND COMBATING BANDITRY IN KATSINA STATE: A SCOPING REVIEW (FUDMA JOURNAL OF SCIENCES, 2025)
Katsina State in northwestern Nigeria faces persistent threats from organized banditry, including mass abductions, arms smuggling, and cross-border crimes. Traditional security measures have demonstrated limited effectiveness in addressing these complex challenges. This scoping review aims to evaluate the potential application of nuclear-based technologies such as radiation detection, remote sensing, and isotopic tracking in enhancing security operations within Katsina State. The review seeks to explore feasibility, identify relevant stakeholders, and assess potential risks and mitigation strategies. The methodology was applied, following Arksey and O’Malley’s framework and PRISMA-ScR guidelines. Literature was sourced from databases including Google Scholar, IEEE, and ScienceDirect, along with IAEA technical reports. Studies included those focused on civilian nuclear security applications, particularly in contexts of border control, anti-smuggling, and regional surveillance. Findings suggest that nuclear-based tools such as mobile radiation detectors, gamma imaging, and UAV-mounted sensors have been successfully used in other conflict-prone or border-sensitive regions. Their integration into Katsina’s security framework could improve early threat detection, enhance intelligence-gathering, and support interdiction of illicit activities. Collaboration with federal agencies and international partners is crucial for pilot deployment and capacity building. Nuclear technologies present viable opportunities for improving security in Katsina State. However, deployment must be accompanied by legal frameworks, stakeholder coordination, and public sensitization to address operational, ethical, and financial concerns. This review recommends phased pilot testing and institutional support to guide sustainable integration.
Keywords: Nuclear-based security technologies; Organized banditry in Nigeria; Remote radiation sensing; Gamma imaging surveillance; Katsina State border control